Legends of CHIMA [videorecording (DVD)] : The lion, the crocodile and the power of chi. - Schantz, Scott
Once a pristine, natural paradise, the Kingdom of Chima has become a battleground for eight animal tribes; best friends vs. enemies. The animals fight for control of a natural resource called CHI, a powerful element that is both a source of life and potential destruction.